The Huns - Kim, Hyun Jin, 1982-, author.
1 online resource (xiv, 193 pages)
Keywords: "The Huns are notorious for their role in European late antiquity. As a consequence however, their history, culture and impact have all been evaluated largely from a Greco-Roman perspective, rather than as an independent historical entity. This book addresses this imbalance. It approaches the history and culture of the Huns in Europe from an Inner Asian and Eurasian perspective, making both their Inner Asian and European history accessible, and also reveals the Huns' contribution to European civilisation and statecraft. It is a crucial tool for students and scholars of late antiquity, and makes available eastern sources that may otherwise be out of the reach of classical historians"--Provided by publisher.